Methylphenidate treatment for severe ADHD in a bone marrow transplant child with DiGeorge's anomaly - (:unkn) unknown (My University, 2005)
As the number of bone marrow transplantations (BMT) performed in the pediatric age group is on the rise, there is a growing need to expand our knowledge of psychopharmacological interventions in this special situation. We report a case who had undergone BMT for congenital immunodeficiency syndrome involving thymus aplasia. He was referred to the child psychiatry department with severe hyperactivity and mental retardation. Taking the necessary medical precautions, methylphenidate was started and continued for over a year. Marked improvement in the symptoms of attention deficit hyperactivity disorder (ADHD) and better adaptation to his educational setting were achieved. No adverse event occurred with regard to his vulnerable immune system.
Keywords: Attention-deficit with hyperactivity disorder (ADHD); Bone marrow; Immune system; Immunodeficiency; Methylphenidate; Transplantation